To solve for \( x \) in the equation \((-x) = -6\), the next step would be to divide both sides by \(-1\). This results in \( x = 6 \).
Therefore, the correct answer is:
B. Divide both sides by -1 to get x=6.
Jackson solved the problem 3x-8=2(2x-7) using the following steps:
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step?
A.
Use Property of Equality to get x= (-6)
B.
Divide both sides by -1 to get x=6
C.
Divide both sides by -1 to get x= (-6)
D.
Use Multiplication Property of Equality to get x=6
1 answer
To solve for \( x \) in the equation \((-x) = -6\), the next step would be to divide both sides by \(-1\). This results in \( x = 6 \).
Therefore, the correct answer is:
B. Divide both sides by -1 to get x=6.